Death Related to a Congenital Vascular Anomaly of Pulmonary Hamartoma Type: Malpractice or Tragic Fatality? - Maricla Marrone; Laura Marrone; Gerardo Cazzato; Stefania Lonero Baldassarra; Giuseppe Ingravallo; Alessandra Stellacci (Medicina, 2021)
In forensic pathology, apparently straightforward cases can often hide rarities that, if not correctly interpreted, can alter the results of the entire investigation, leading to misinterpretations. This occurs when the investigation is conducted to assess medical malpractice. An unexpected death, with no known apparent cause, is often linked to an underlying disease process of unclear etiological origin whose nature can, unfortunately, be properly investigated only post-mortem. This presentation shows a case study, in which it was possible to reconduct the death of a patient to a natural pathology and not to medical treatment. Here, the authors illustrate a case with a hamartoma developed in chronic inflammatory conditions (bronchiectasis) that was difficult to differentiate from lung cancer due to the inability to perform specific instrumental examinations. The hamartoma, usually benign and identifiable by standard instrumental investigations, in this case, led to the patient’s death precisely during the execution of a bronchoscopy. However, in the absence of a certain cause of death, public opinion unanimously attributes a patient’s disease to medical error. Indeed, a routine practice such as bronchoscopy should not cause death and consequently, the doctor must have made a mistake. Fortunately, the autopsy not only demonstrated the origin of the bleeding but also unveiled the reason for this, as rare congenital lung disease. Fate, one might say.